Computer simulation of microwave cooking of sweet potato. (21st July 2022) - Kako, Yoshihiro; Llave, Yvan; Sakai, Noboru; Fukuoka, Mika
Abstract: Although sweet potatoes have the characteristic of becoming sweeter when heated, the MW treatment is challenging because its characteristic high heating rate can affect the intrinsic chemical changes of sweet potatoes during MW heating. To clarify this phenomena, experimental and simulated approaches for the microwave (MW) cooking of sweet potatoes were evaluated. The dielectric properties (DPs) of sweet potatoes during MW heating were measured from 20 to 90°C at 2450 MHz. A three‐dimensional (3D) geometric model based on the actual structure and size of the MW flatbed oven and sample was constructed. Two commercial software packages, which are based on the finite element method (FEM) were used for the calculation by coupling the analysis of electromagnetic fields and heat transfer. To improve the calculation during temperature simulation, a mathematical approach considering a contact layer for the boundary between the sample and the ceramic plate was evaluated. The dielectric constant decreased with increasing temperature; whereas, the dielectric loss factor values were similar at 20–60°C. However, at 60–90°C, the values decreased sharply. The temperature change inside the sweet potato was estimated using the 3D model and temperature profiles and cross‐section distributions were compared with the experimental results. The simulated results agree well to the measured results especially for the approach considering a contact layer for the surrounding air below the samples. These results are of potential value for the design of MW cooking systems for sweet potatoes. Practical Applications: The applications of the findings of this study include but are not limited to: (a) use the measured DPs of sweet potatoes in both industrial applications and academia for developing novel applications of microwaveable sweet potato‐based products, (b) predict the temperature profiles and distributions of sweet potatoes using the developed 3D computer simulation model for MW heating in flatbed ovens, and (c) improve the simulation of MW heating of foods directly placed on the ceramic plate during MW treatment considering the contact layer approach evaluated in this study.